PENGALAMAN PERAWAT DALAM MERAWAT PASIEN COVID-19 DI RUANG ISOLASI RSUD BALARAJA - Kristina Everentia Ngasu; Nabilla Ainiyyah; Zahrah Maulidia Septimar (Yayasan Nusantara Hasana Berdikari, 2023)
COVID-19 has placed a huge burden on the health care system, especially on health workers who are directly involved in handling COVID-19 patients. One of the burdens experienced by health workers is mental disorders such as anxiety, fear, stress, depression, panic, sadness, frustration, anger, and denial. Objective of this study to find out the Experience of Nurses in Caring for COVID-19 Patients in the Isolation Room of the Balaraja Hospital. The method used is qualitative research. The data analysis in this study used a verbatim script. Verbatim identification of key questions. Researchers carried out an internal interpretation process, data analysis tables, Participants' experiences. Psychological changes experienced by participants can be seen from the participants' expressions which stated that they were anxious about being exposed. the Covid-19 virus, the role and support received by participants can be seen from the participants' expressions which state that support from the family plays an important role in carrying out their duties as nurses for Covid-19 patients. Nurses get a lot of new experiences, such as new knowledge about Covid-19 and life experience.